2019
DOI: 10.4028/www.scientific.net/amm.887.553
|View full text |Cite
|
Sign up to set email alerts
|

A Cell-Based Method to Support Hospital Refurbishment

Abstract: Hospital refurbishments often take place in parallel to regular operation, resulting in a scheduling problem: Construction activities must located such as they do not clash with daily work activities and vice versa. To be able to see this mutual influence, we have devised a tool in which we are able to visualize the adverse effects of construction on daily operation. The approach uses a cellular automaton to represent the three-dimensional hospital environment and uses a particle simulation for computing the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The Spanish hospital stock represents 3% of non-residential buildings [3] and is on average over 25 years old [4]. The equipment's antiquity, combined with stringent demand specifications, means that hospitals are neither energy nor environmentally efficient [5]. Kolokotsa et al [6] compiled technologies and strategies to promote energy savings and a reduction of CO 2 emissions in hospital facilities and concluded that a series of measures can save up to 10% of primary energy while taking into account that the level of services provided in a hospital cannot be reduced [7].…”
Section: Introductionmentioning
confidence: 99%
“…The Spanish hospital stock represents 3% of non-residential buildings [3] and is on average over 25 years old [4]. The equipment's antiquity, combined with stringent demand specifications, means that hospitals are neither energy nor environmentally efficient [5]. Kolokotsa et al [6] compiled technologies and strategies to promote energy savings and a reduction of CO 2 emissions in hospital facilities and concluded that a series of measures can save up to 10% of primary energy while taking into account that the level of services provided in a hospital cannot be reduced [7].…”
Section: Introductionmentioning
confidence: 99%